Towards a new Index of Multiple Area‐Level Deprivation for Auckland, New Zealand. (20th April 2016) - Exeter, Daniel J.; Zhao, Jinfeng; Browne, Michael; Lee, Arier C.
Abstract : We explore the feasibility of developing measures of area deprivation from routinely collected administrative data for the Auckland Region, based on the Scottish Indices of Multiple Deprivation. Using data from national health, social development, education, and police databases, geospatial data providers and the 2006 Census, we developed seven domains of deprivation: Employment; Income; Crime; Housing; Health; Education; and Geographical Access, which were combined to create an overall Index of Multiple Area‐Level Deprivation.Small areas developed for this research ('Lower Zones') highlight variations in deprivation for domains separately and combined, and validate the indices using smoking prevalence data.